An exploratory study of the effects of cultural capital on the successful completion of a two-year honors program - Button, Ryan Lewis (Kansas State University, 2017)
It has been assumed that community college students are comprised of students who are either not ready for the rigors of a four-year college experience and/or students who are only interested in receiving a degree in a technical field. With concerns of rising debt, largely associated with colleges being forced to turn to tuition as a major revenue source, the validity of these assumptions merits a better understanding to how the economic atmosphere has changed the demographics of students at a two-year institution, let alone the demographics of an honors student population. Further, little-to-no analysis has looked at the effects of the ascriptive characteristics of students beyond parent’s income and occupation in determining academic success in a two-year honors program. To answer these concerns, I examine how institutional, family, and individual level factors affect the successful completion of an honors program by students attending a two-year junior college. It is the objective of this research to arrive at a better understanding of two primary questions: first, what are the characteristics and backgrounds of honors students at a two-year college; second, what are the determinants of academic success at a two-year honors program? It is hypothesized that exposure to cultural capital by students, prior to and while attending junior college, is important in facilitating academic success. Quantitative methodology is used to examine the research questions and test the study hypotheses concerning the effects of cultural capital on successful completion from a two-year college honors program. Data were collected from college students enrolled in the honors program at Tyler Junior College, a two-year college located in Tyler, Texas. The findings report that exposure to culture capital does have a positive effect on students’ graduating from a two-year college honors program.
Keywords: Cultural capital